Of Landscapes and Animals: An Ecosophical Analysis of Pagu Folktales - Novita Dewi (JURNAL ARBITRER, 2020)
Spoken by a few members of the Pagu ethnic group in North Halmahera province, Pagu is one among endangered languages in Indonesia worth saving from extinction (Perangin-Angin, 2018). This study examines the preservation of Pagu by caring for the literary wealth in the language, i.e., folktales. Using Ecosophy as a theoretical trajectory, the analysis of the five Pagu folktales studied show that (1) Two creation fables are anthropocentric because the intention is to teach and impart values to people; (2) The other two are morality tales calling for people's care for and attention to the environment and all the ecosystems which have so far supported people's life. This study concludes that not only do traditional tales enhance language research and character education, they also deliver transformative power to call for an ethic of care – caring for the language and caring for the environment. Thus, the maintenance of the local culture, such as folktales, complements the language preservation efforts.